2017
DOI: 10.1159/000475840
|View full text |Cite
|
Sign up to set email alerts
|

The Home Literacy Environment of Preschool-Age Children with Autism or Down Syndrome

Abstract: Aims: This exploratory study investigated if there were differences in the home literacy environment of preschool children on the autism spectrum and preschool children with Down syndrome to determine if the home literacy environment may potentially be associated with strengths or weaknesses in children’s social communication skills. Methods: A total of 111 parents of preschoolers with identified disabilities completed a home literacy questionnaire. Results: Results indicated that both groups of parents starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…Inclusion of special interests were frequently reported by parents as motivating their child to participate in literacy activities. Children on the autism spectrum have been found to demonstrate lower levels of interest in reading activities than peers with other disabilities, such as Down syndrome (Westerveld & van Bysterveldt, 2017), which may account for some of these engagement difficulties. Language delays (receptive and/or expressive) were also identified as a commonly encountered challenge that hindered the child's ability to effectively participate in literacy learning.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of special interests were frequently reported by parents as motivating their child to participate in literacy activities. Children on the autism spectrum have been found to demonstrate lower levels of interest in reading activities than peers with other disabilities, such as Down syndrome (Westerveld & van Bysterveldt, 2017), which may account for some of these engagement difficulties. Language delays (receptive and/or expressive) were also identified as a commonly encountered challenge that hindered the child's ability to effectively participate in literacy learning.…”
Section: Discussionmentioning
confidence: 99%
“…The parent survey used was based on the early literacy parent questionnaire developed by Boudreau (2005) consistent with previous research by Westerveld and van Bysterveldt (2017). It included a total of 27 questions regarding early literacy (child response to reading books, response to print, and interest in letters), demographics of child and parent, and for the purposes of this study, additional questions regarding library visits, attendance of early literacy sessions, reasons for non-attendance of such sessions (checklist to indicate barriers present such as time), and interest in attending a 4-6 week early literacy (Storytime) program in a local library were included.…”
Section: Methodsmentioning
confidence: 99%
“…This research has focused on typically developing children and is well established (Hood et al 2008;Sénéchal 2006;Sénéchal and LeFevre 2002;Sénéchal et al 2008). The emerging research investigating the home literacy environment of children who have autism would suggest differences in these environments of children who have autism (Lucas and Norbury, 2018;Westerveld and van Bysterveldt, 2017). To illustrate, Westerveld and van Bysterveldt (2017) found that although parents of children who have autism reported exposing their children to books from an early age and owning a range of children's books, compared to parents with preschool children with Down syndrome, they reportedly read to their children less frequently reported a lower interest in books by their children who have autism.…”
mentioning
confidence: 99%
“…Justice & Kaderavek, 2002). However, a recent study conducted by Westerveld and van Bysterveldt (2017) with parents of children with ASD found that while shared book reading was part of many families' routines, young children with ASD showed lower interest in shared book reading as an activity compared to their peers with Down syndrome. However, whether differences between children with ASD and other groups exist in their engagement with different types of books in the home environment, which could be further influencing their learning opportunities in the early years, has not been investigated.…”
Section: Introductionmentioning
confidence: 97%